Analysis of discharge process of oil pipeline with complex topography. (November 2019) - Liu, Enbin; Ma, Xi; Zhou, Mo
Abstract: During the commissioning process of "first injection of crude oil after water injection", due to the density difference between crude oil and water, the oil pressure on the left side of the "U" section is less than the right hydraulic pressure, and the running process of the oil head is stagnated in a hilly oil pipeline with high elevation difference. Concerning this problem, solution of discharging pressure by using relief valve in valve station nearby oil–water interfacial point is proposed in this paper. According to the actual data, gas–liquid flow in a gas-cap empty process of a big drop and hilly oil pipeline was numerically investigated by dynamic multiphase simulation software OLGA. Simulation data in terms of flow rate, pressure and leakage were compared under different leaking apertures. The simulation results show that the general pressure variation tendencies at the vent, bottom point or top and low elbows show no connection with vent diameters but its final fluctuation that the smaller the diameter is, the more intensive the fluctuation gets.. And as for the emptying of a big drop and hilly pipeline, appropriate increase of leaking aperture can improve the drainage ratio (leakage/general capacity of the pipeline) and drainage rate, but excessive aperture will cause severe negative pressure and breakage cavity which foster the likelihood of close water-surge and damage to the pipe safety.